(untitled) (European Journal of Mental Health, 2010)
Emergency Counsellors in Germany: Since the mid-90s, emergency counsellors in Germany have often assumed the support of persons that are more severely affected by an emergency and require emergency counselling. This group of people who need further emergency support includes people who are directly affected by the emergency, but also persons that are affected indirectly, affiliated, eye-witnesses and causers. Within the framework of these chores, emergency counsellors deliver for example in cooperation with the local police death notices or support parents whose child has died unexpectedly. The support of the direct and indirect emergency victims is basically carried out in their own homes. This requires particular sensitivity of the emergency counsellors, since they are welcomed as guests, but at the same time have to conduct the setting. Emergency counsellors are summoned in emergencies that record dead and dying persons. The central offices of the fire brigade alert the emergency counsellors, but the task forces in situ may also request emergency counsellors. The cooperation of emergency counsellors and other task forces such as police or rescue services is established to a large extent. However, the cooperation is not performed very easily, which is due to various reasons such as the heterogeneous organisational structures of the individual task forces. A catastrophe constitutes a particular challenge to emergency counsellors as decisions have to be undertaken under time pressure and with a lack of resources. Victims of emergencies may be exposed to extreme stress, which can be distinguished into physiological stress like pain and psychological stress such as loss of control. The consequences resulting from the experienced stress are determined by biological, sociographic and psychological facilitating variables, which may function in a reinforcing or relieving fashion. The assigned jobs of task forces and the behaviour of emergency counsellors further influence the consequences of emergencies. Thus, the reactions and consequences of emergencies may vary to a large extent. The support of people affected by emergencies comprises usually one session, which may vary in length. If required, contacts to professionals should be established. The work of emergency counsellors is characterised by the activation of the emergency victim’s inner and outer resources. A further important step is the education in psychological matters for directly and indirectly affected people. The prerequisite for a professional course of action is a good training for emergency counsellors. In the future the goal is to have a uniform nationwide training. Quality checks and evaluations should be carried out for the work of emergency counsellors. In addition, the alerting of emergency counsellors should be embedded into emergency schemes.